Small Business, Big Impact: The Role of SMEs in Galápagos Conservation - Valencia, Paola; Pohlmann, Attila; Cristóbal-Fransi, Eduard (Journal of Ecohumanism, 2024)
The Galápagos Islands, a UNESCO World Heritage Site since 1978, face increasing ecological pressure from tourism development and the consequences of its growth. This study explores SMEs' perspectives on ecohumanism, sustainability, and environmental responsibility through thematic analysis of in-depth interviews with several owners and managers. Key findings include: a growing awareness of the environmental degradation caused by tourism; efforts by SMEs to implement sustainable practices in their businesses, such as reducing waste, using local products, and engaging tourists in conservation activities; recognition of the need for stronger government regulations and community involvement in sustainable tourism; and a tension between economic growth and environmental protection. SMEs can play a crucial role in fostering better environmental stewardship through providing residents with tourist-like experiences. Collaborative efforts among businesses, governments, and communities are essential for balancing economic benefits with long-term conservation.